(untitled) (Modern education and development, 2025)
In the information age, the forms, methods and scope of manipulation and persuasion are expanding, posing a serious threat to the individual, society and culture. The article studies the conflict of manipulation and persuasion with moral norms, values and cultural traditions, as well as their impact on the principles of social justice, equality and democracy. The ethical, cultural and socio-philosophical foundations of combating manipulation and persuasion in the information age are analyzed, in particular, such areas as ensuring information security, increasing media literacy, developing critical thinking and promoting moral values. It is significant that the article is aimed at a deep understanding of the ethical, cultural and socio-philosophical problems of manipulation and persuasion in the information age and finding ways to solve them.